Pengaruh kegunaan, kesesuaian, keuntungan, motivasi, dan risiko terhadap niat perilaku pada mobile banking Bank Mandiri di Surabaya - Muhammad Ilham Mandrata; Yudi Sutarso (STIE Perbanas Surabaya, 2019)
Mobile banking, as a banking service, has been popular in a couple of years. In Indonesia, many banks have already this kind of service. The study aims to examine the influence of perceived usefulness, compatibility, relative advantage, hedonic motivation, and perceived risk on customer’s behaviour intention to use mobile-banking of Bank Mandiri in Surabaya. In this research, the data were collected by questionnaires distributed to 125 respondens, using Mandiri mobile-banking. They were selected based on judgement sampling. The data were analyzed using partial least square. It shows that perceived usefulness and relative advantage have a positive effect on behavior intention, but compatibility and hedonic motivation has not. Besides that, perceived risk has negatif effect on the intention to use mobile banking service.